Governmental Liquidities Management 2008-2010 - Dumitru, Andrei Laurentiu; Vlad, Cristina; Brezeanu, Petre (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2015)
This article opens a suite dedicated to State Treasury financial structure optimization. It further develops our previous excursus on State Treasury mechanism, operation policies and practice, alignment to EU regulations, and the influence of fiscal pressure on the EU states economies. This article concentrates on risk prevention and containment of the possible impact. It further describes the financing policy that has been adopted. The following section describes the effects of the applied policies and practice, as well as the accessed financial package. We have included a lessons learned section, to outline what we strongly believe should achieved for enriching the data sets and processing automation – these being instrumental to ensure the accuracy and relevance of the decision process and actions. We finally project the main theme of the future articles and to outline the need of competitive central administration partner for the national business community – which is tightly and ever tighter connected to its global counterparties.